Implementation of the Third Mission of the Universities: Regional Aspect //Implementación de la Tercera Misión de las Universidades: Aspecto Regional - Shumik, Ekaterina G.; Baturina, Olga A. (Revista de la Universidad del Zulia, 2020)
AbstractNational economic growth plays an important role in the education rate of society, since there is a strong connection between the success of the country and the level of development of human capital. In this sense, universities, as leaders of higher education, can powerfully affect the socio-economic development of society. In this article, the authors investigated different models of university development with the intention of determining the importance of their association. In addition, the authors evaluated the level and trends of the development of alliances between the universities of the Far Eastern Federal District (FEFD) as a tool for the implementation of their mission. To do this, they analyzed the websites of FEFD universities to reflect data on common activities within social activities. They also did a comparative analysis to compare the characteristics of the universities and evaluate the differences in the implementation of the social function. Finally, the correlation analysis was used to determine the effect of social events, the number of students and the university ranking. Based on these analyzes, it can be concluded that most of the universities are located in three regions: Primorsky and Khabarovsk Territories, as well as the Republic of Sakha (Yakutia), which are pioneers in terms of the number of students. While there is a tendency to reduce government involvement in university support, the FEFD increases. In addition, it has been shown that there is a relationship between the position in the ranking of universities in the region and the number of social events. Regarding the structure of university activities in matters of social responsibility, the development of university partnership interactions in the process of implementation of social responsibility has been verified, but the level of formalization of relationships is extremely low.Resumen El crecimiento económico nacional juega un papel importante en la tasa de educación de la sociedad, ya que existe una fuerte conexión entre el éxito del país y el nivel de desarrollo del capital humano. En este sentido, las universidades, como líderes de la educación superior, pueden afectar poderosamente el desarrollo socioeconómico de la sociedad. En este artículo, los autores investigaron diferentes modelos de desarrollo universitario con la intención de determinar la importancia de su asociación. Además, los autores evaluaron el nivel y las tendencias del desarrollo de alianzas entre las universidades del Distrito Federal del Lejano Oriente (FEFD) como una herramienta para la implementación de su misión. Para ello, analizaron los sitios web de las universidades FEFD para reflejar datos sobre actividades comunes dentro de las actividades sociales. También hicieron un análisis comparativo para comparar las características de las universidades y evaluar las diferencias en la implementación de la función social. Finalmente, se utilizó el análisis de correlación para determinar el efecto de los eventos sociales, el número de estudiantes y el ranking universitario. Según estos análisis, se puede concluir que la mayoría de las universidades están ubicadas en tres regiones: Territorios de Primorsky y Khabarovsk, así como la República de Sakha (Yakutia), que son pioneras en cuanto al número de estudiantes. Si bien existe una tendencia a reducir la participación del gobierno en el apoyo a la universidad, aumenta el FEFD. Además, se ha demostrado que existe una relación entre la posición en el ranking de las universidades de la región y el número de eventos sociales. En cuanto a la estructura de las actividades universitarias en materia de responsabilidad social, se ha comprobado el desarrollo de las interacciones del partenariado universitario en el proceso de implementación de la responsabilidad social, pero el nivel de formalización de las relaciones es extremadamente bajo.